2012
DOI: 10.1016/j.aquaculture.2011.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary palm oil supplements with oxidized and non-oxidized fish oil on growth performances and fatty acid compositions of juvenile Japanese sea bass, Lateolabrax japonicus

Abstract: The aim of the present study was to investigate the effects of replacement of fresh fish oil (FFO) by palm oil (PMO) and/or oxidized fish oil (OXF) mixed with PMO on growth performances, tissue fatty acid composition and oxidative status in juvenile Japanese sea bass. A 50-day feeding trial on Japanese sea bass (average weight 1.7 g) was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 31 publications
6
41
1
Order By: Relevance
“…Fish oil sparing rarely impacts fish production performance as long as essential fatty acid requirements are met (Turchini et al , 2011aGao et al 2011;Trushenski et al 2011aTrushenski et al , 2011bTrushenski et al , 2011cTrushenski et al , 2011dTrushenski et al , 2013aTrushenski et al , 2013bKamarudin et al 2012;Mulligan and Trushenski 2013;Ng et al 2013;Trushenski and Kanczuzewski 2013). Our results are consistent with this convention and with other research on fish oil sparing in Cobias (Trushenski et al 2011a(Trushenski et al , 2012(Trushenski et al , 2013bWoitel et al 2014).…”
Section: Discussionsupporting
confidence: 95%
“…Fish oil sparing rarely impacts fish production performance as long as essential fatty acid requirements are met (Turchini et al , 2011aGao et al 2011;Trushenski et al 2011aTrushenski et al , 2011bTrushenski et al , 2011cTrushenski et al , 2011dTrushenski et al , 2013aTrushenski et al , 2013bKamarudin et al 2012;Mulligan and Trushenski 2013;Ng et al 2013;Trushenski and Kanczuzewski 2013). Our results are consistent with this convention and with other research on fish oil sparing in Cobias (Trushenski et al 2011a(Trushenski et al , 2012(Trushenski et al , 2013bWoitel et al 2014).…”
Section: Discussionsupporting
confidence: 95%
“…Comparatively, values in the liver and muscle were smaller compared that of the feed indicating that LA was used to the meet energy demands of the fish (Li et al, 2016). Inclusion of dietary PO resulted in a significant decrease of n-3 PUFA in both liver and muscle (from 10.16 to 2.77 and 7.59 to 4.18 respectively), and is in agreement with other studies (Mourente and Bell, 2006;Gao et al, 2012). Contrary to this study, Visentainer et al (2005) observed a significant increase in n-3 fatty acids in adult Nile tilapia fed diets with increasing levels of flaxseed oil.…”
Section: Discussionsupporting
confidence: 81%
“…Lower quantity of PUFA n-3 in the diets reduces fish susceptibility to these oxidative reactions. This fact has been demonstrated in a seabass Lateolabrax japonicus study, in which the fish were fed with diets that contained palm oil associated with fish oil and presented lower malondialdehyde levels (MDA) (GAO et al, 2012). The ingested PUFAs are stocked in the liver and are susceptible to peroxidation due to the activation of the peroxisome proliferator-activated receptor (PPARα) that produces hydrogen peroxide and causes tissue damages.…”
Section: Resultsmentioning
confidence: 98%